Institusi fatwa dalam perundangan negara: Satu penilaian menurut siasah syar’iyyah - Hasnan Kasan, (Universiti Kebangsaan Malaysia, 2001)
The fatwa intitution in Malaysia is the institution which provides the guide line for the practice of the muslim in the country. The study attempts to look into the fatwa released by the fatwa institution within the scope of the country legal system with emphasize to the appointment Mufti, the procedure to arrive at a particular fatwa and the fatwa enforcement